The NEDD4/FLRT2 axis regulates NSCLC cell stemness - Yang, Yuping; Yan, Fei; Gao, Ziwei; Li, Houke; Wen, Shengke; Li, Qi; Li, Jiayuan; Huang, Na; Zhao, Wei (Frontiers in Pharmacology, 2024)
Introduction Lung cancer is the leading cause of cancer-related death worldwide. The treatment for lung cancer, particularly for non-small cell lung cancer (NSCLC), remains a clinical challenge. Cancer stem cells are vital for lung cancer development. This study aimed to determine the influence of the neuronally expressed developmentally downregulated 4-fibronectin leucine-rich transmembrane 2 (NEDD4-FLRT2) axis on cancer cell stemness in NSCLC. Methods FLRT2 expression in NSCLC tissues and stem cells was investigated using western blot and RT-qPCR. The sphere formation assay and the abundance of stemness markers were employed to confirm the stemness of NSCLC stem cells. The CCK-8, colony formation, and Trans-well assays, as well as flow cytometry, were used to determine NSCLC stem cell growth, metastasis, and apoptosis, respectively. The Co-IP assay was used to confirm the binding between NEDD4 and FLRT2. Xenograft tumor mouse models were used to investigate tumorigenesis in vivo. Results Here, we reported that FLRT2 expression was reduced in NSCLC tissues, cells, and NSCLC stem cells. FLRT2 upregulation inhibited NSCLC stem cell proliferation, sphere formation, and drug resistance and promoted drug-resistant cell apoptosis. Furthermore, FLRT2 overexpression demonstrated antitumor effects in a xenograft tumor mouse model. Mechanically, FLRT2 was ubiquitinated and degraded by E3 ligase NEDD4. NEDD4 overexpression significantly abolished the inhibitory effects of FLRT2 on NSCLC stemness, as evidenced by in vitro and in vivo experiments. Discussion This study revealed that FLRT2 acted as a tumor suppressor by inhibiting cancer cell stemness in NSCLC. NEDD4 promoted ubiquitination degradation of FLRT2 protein. NEDD4 counteracted the inhibitory effects of FLRT2 on NSCLC stem cell tumorigenesis.